Reconfiguring the Legal Standing of Baitul Maal wat Tamwil: Examining the Tension between Cooperative and Corporate Models in Indonesia - Novi Kusumawati; Barhanudin Harahap (Rule of Law Studies Journal, 2025)
Background; Baitul Maal wat Tamwil (BMT) plays a dual role by combining community welfare with financial services. The enactment of the 2013 Microfinance Law, however, obliges BMT to operate either as a cooperative or a limited company, producing uncertainty about its legal foundation. Aims; This paper seeks to clarify the legal position of BMT and to assess how this regulatory demand influences its original character and the development of Islamic microfinance in Indonesia. Methods; Using a normative juridical method, the study reviews statutory provisions, legal doctrines, and academic debates. The comparison of cooperative and corporate frameworks with Islamic financial principles is used to highlight regulatory gaps and tensions. Result; The findings suggest that the cooperative option preserves BMT’s communal values, while the corporate path offers efficiency and capital access. Both, nevertheless, may undermine the institution’s hybrid nature as a socio-financial body. Conclusion; The study concludes that BMT faces an unresolved tension between legal compliance and mission continuity. To maintain its distinctive role, policymakers should craft regulations that acknowledge BMT’s hybrid identity and strengthen its contribution to inclusive economic growth.